ANALISIS STRATEGI KOMUNIKASI PEMASARAN TERPADU UNTUK MENINGKATKAN LOYALITAS KONSUMEN PADA TOKO SYARAH BAKERY - Puspitasari, Yosi Ririn; Ratnawili, Ratnawili (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
This study aims to determine the Integrated Marketing Communication Strategy to Increase Consumer Loyalty at the Syarah Bakery Shop. This research uses a qualitative research method. The informants in the research in this study are the Owner and Field Employees of the Syarah Bakery Shop. The data collection method is by conducting interviews and documentation. The data analysis technique used is SWOT Analysis. From this research it is known that the Integrated Marketing Communication Strategy to Increase Consumer Loyalty at the Svarah Bakery Shop is (1) Maintaining Product Quality (2) Adding Product Variants (3) Increasing Products (4) Opening Branches While the promotions carried out by Syarah Bakery Shop are still not attractive even though promotion is one way to increase consumer loyalty. Keywords: Integrated Marketing Communication Strategy. Loyalty   Consumer